2006
DOI: 10.1186/1748-717x-1-44
|View full text |Cite
|
Sign up to set email alerts
|

Intensity Modulated Radiotherapy (IMRT) in the postoperative treatment of an adenocarcinoma of the endometrium complicated by a pelvic kidney

Abstract: Background: Pelvic Radiotherapy (RT) as a postoperative treatment for endometrial cancer improves local regional control. Brachytherapy also improves vaginal control. Both treatments imply significant side effects that a fine RT technique can help avoiding. Intensity Modulated RT (IMRT) enables the treatment of the target volume while protecting normal tissue. It therefore reduces the incidence and severity of side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…have reported a case of carcinoma of endometrium treated with adjuvant IMRT and the follow up renal evaluation was shown to be normal [22] . The observations made in this study are different from that of the previous studies but, the range of associated anomalies is the same.…”
Section: Discussionmentioning
confidence: 99%
“…have reported a case of carcinoma of endometrium treated with adjuvant IMRT and the follow up renal evaluation was shown to be normal [22] . The observations made in this study are different from that of the previous studies but, the range of associated anomalies is the same.…”
Section: Discussionmentioning
confidence: 99%
“…10 Castilho et al treated a postoperative case of carcinoma of the endometrium with pelvic kidney with a dose of 45 Gy using IMRT. 11 Two-thirds of the ectopic kidney received 21 Gy and one-third received 31 Gy. The patient suffered no recurrence or side effects to either kidney at 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Castilho et al reported in 2006 the first use of IMRT for an endometrial cancer patient with a congenital pelvic kidney. [8] Seven co-planar fields covered 95% of the whole pelvis and lymphatics to 45 Gy. The ectopic kidney was centrally located in the pelvis at the level of the sacro-iliac joints.…”
Section: Discussionmentioning
confidence: 99%